ANALISIS PENGARUH PEER-TO-PEER LENDING TERHADAP KINERJA KELOMPOK BANK DENGAN MODAL INDIKATOR KESEHATAN EMPAT (KBMI 4) - Kristwanda, Princess Natalie Budi; Satria, Dias (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Over the years, the world of technology and innovation has evolved. One of them is the financial sector, namely financial technology (fintech). This study aims to determine how the presence of peer-to-peer lending in Indonesia can have an impact on banking performance in Indonesia, proxied by return on assets (ROA) because it is indicated that fintech cuts the market segmentation of banks. The variables used are the number of companies, the number of lenders, the number of borrowers, and the number of loans whose data is taken from the Financial Services Authority. This type of research is quantitative research using the Error Correction Model (ECM) method approach. The result of this research is that the presence of peer-to-peer lending will synergize with KBMI 4 Bank and produce a mutually beneficial relationship.